2012
DOI: 10.1111/j.1537-2995.2011.03532.x
|View full text |Cite
|
Sign up to set email alerts
|

The cost of blood transfusion in Western Europe as estimated from six studies

Abstract: The estimated cost of transfusing 2 units of RBCs in Western Europe is significant. Differences in methodology were partially diffused by aggregation of prior estimates into a population-weighted mean. Future cost studies should follow the Cost of Blood Consensus Conference (COBCON) recommendation to apply activity-based costing methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 16 publications
1
52
0
Order By: Relevance
“…Each patient who undergoes a transfusion accrues a cost for each unit of allogeneic blood transfused at a cost of €320 per unit [36]. All patients assigned to the PAD blood management strategy who are eligible to receive autologous blood transfusion incur a cost of €500 for the two units of blood donated and stored [37].…”
Section: Methodsmentioning
confidence: 99%
“…Each patient who undergoes a transfusion accrues a cost for each unit of allogeneic blood transfused at a cost of €320 per unit [36]. All patients assigned to the PAD blood management strategy who are eligible to receive autologous blood transfusion incur a cost of €500 for the two units of blood donated and stored [37].…”
Section: Methodsmentioning
confidence: 99%
“…Due to improved collection, testing and processing, the direct costs of blood products have progressively increased (Kamper-Jorgensen et al 2010 ;Abraham and Sun 2012 ). As stated in the introduction, the known and hidden costs have been estimated to be USD 2,000 (Ferraris et al 2012 ;Shander et al 2010 ) per RBC unit.…”
Section: Implementation Of Patient Blood Managementmentioning
confidence: 98%
“…[28][29][30] Toner et al 30 recently reported national mean acquisition costs of $210.74 (7$37.90) per unit of erythrocytes with considerable variation based on geography and facility. In the surgical setting, Shander et al 31 reported on activity-based costs associated with erythrocyte transfusion and found that expenses were generally underestimated by three-to four-fold from acquisition costs.…”
Section: Economicsmentioning
confidence: 99%